Visitor Perceptions of Ancient Egyptian Human Remains in Three United Kindom Museums - Hugh Kilminster (Papers from the Institute of Archaeology, 2003)
Although the issues of retention and display of human remains have become topical over the last decade, the thoughts of museum visitors about this topic have not been registered, despite their being the museums’ main stakeholder. The vast majority (82.5%) of 300 respondents questioned in the summer of 2002 at three British museums displaying ancient Egyptian human remains supported the idea of having these remains on display. However, a small percentage of visitors (14.2%) wanted the remains displayed in a "more appropriate and respectful environment", and this may be the key future challenge for collections with human remains that have no cultural descendants. This paper summarises research into visitor perceptions of ancient Egyptian human remains in museum collections and on display in the United Kingdom and suggests further research into the various aspects of human remains in museums, particularly regarding more recent remains or those with cultural descendants.
Keywords: museums; human remains; Egypt